Mechanical performance of double gated injected metallic looking polypropylene parts - Costantino, María Alejandra (2015)
The metallic effect obtained by incorporation of metal particles in polymers by injection molding has the advantageof eliminating post-processing techniques reducing production cost and time. Nevertheless, undesired defects in thefinal appearance of parts are common. In this work PP/aluminum pigments were obtained by direct injection molding andthe influence of metallic particles on the aesthetic, morphological and mechanical properties of the parts was assessed. Aestheticaspects could be improved by manipulating processing conditions: high melt temperatures diminished differentialshrinkage and made weld lines less noticeable. Also at high melt temperatures Al particles increased thermal conductivityof PP generating a thicker skin, which combined with an inherent gradient temperature and typical shear stresses developedduring injection molding, induced the formation of !-PP phase. Mechanical performance of parts showed to be dependenton PP morphology. Distinct deformation behaviors were seen according to the presence of PP polymorph, !-PP counteractingthe detrimental effect of not bonded Al flakes, and making PP-Al moldings to have similar toughness as PP moldingswith the added value of metallic looking.